Pathological spectrum of glomerular disease in patients with renal insufficiency: a single-center study in Northeastern China - Chen, Liangmei (Ren Fail, 2019)
Background: To investigate the pathological spectrum of glomerular disease in patients with renal insufficiency (RI) from 2008 to 2017. Methods and results: We calculated the estimated glomerular filtration rate (eGFR) with the Chronic Kidney Disease Epidemiology Collaboration creatinine (CKD-EPI) equation and defined RI as an eGFR <60 ml/min/1.73 m(2). A total of 969 RI patients were included in our study. IgA nephropathy (IgAN) was the most common subtype of primary glomerulonephritis (37.2%). The frequencies of IgAN and non-IgA mesangioproliferative glomerulonephritis decreased from 27.3% and 9.5% during 2008–2012 to 20.7% and 2.6% during 2013–2017, respectively. However, the frequency of membranous nephropathy increased from 6.8% to 16.2%. Lupus nephritis was the most common subtype of secondary glomerulonephritis (32.1%). The frequencies of both ANCA-associated systemic vasculitis and diabetic nephropathy increased from 3.8% to 7.6% and from 4.3% to 7.6%, respectively. The number of elderly patients (≥60 years) in our study increased sharply, from 15.6% in 2008 to 35.0% in 2017. Membranous nephropathy, minimal change disease, membranoproliferative glomerulonephritis, lupus nephritis and renal amyloidosis are more frequently observed in the elderly patients than in nonelderly patients (<60 years) (p < .05). Excluding those with acute kidney injury, IgAN was the leading cause of RI (24.9%), followed by membranous nephropathy (13.3%) and lupus nephritis (12.0%). Conclusions: IgAN and lupus nephritis were the most prevalent primary glomerulonephritis and secondary glomerulonephritis in patients with RI, respectively. The frequencies of membranous nephropathy, ANCA-associated systemic vasculitis and diabetic nephropathy increased significantly. The number of elderly patients with RI increased sharply.